2010
DOI: 10.1097/jom.0b013e3181d5e355
|View full text |Cite
|
Sign up to set email alerts
|

An Estimate of Cancers Attributable to Occupational Exposures in France

Abstract: Our estimates are comparable with those obtained for other countries in studies based on similar methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 29 publications
3
26
1
2
Order By: Relevance
“…Occupational exposures are the second major risk factor for lung cancer, and the attributable risk fraction is approximately 15% to 30% in men and 3 to 6% in women [13]. However, the occupational lung carcinogens that have been identified thus far are found almost exclusively in male occupations (e.g., building, metallurgy, mining).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational exposures are the second major risk factor for lung cancer, and the attributable risk fraction is approximately 15% to 30% in men and 3 to 6% in women [13]. However, the occupational lung carcinogens that have been identified thus far are found almost exclusively in male occupations (e.g., building, metallurgy, mining).…”
Section: Introductionmentioning
confidence: 99%
“…Industrial Health 2013, 51, [128][129][130][131][132][133] Original Article Goodman 3) , which are based on meta-analysis of cohort studies, as in French 4) and UK 5) studies. World Health…”
Section: ©2013 National Institute Of Occupational Safety and Healthmentioning
confidence: 99%
“…We used a PAR of 11.6% estimated from a Dutch case–cohort study 7. Although this estimate appears to be reasonable compared with other studies, higher and lower PARs have also been reported 5 6 32 33. A systematic review of asbestos-related cancer in Europe estimated the PAR to be between 5.7% and 19% 32.…”
Section: Discussionmentioning
confidence: 99%